Associations between belief in conspiracy theories and the maladaptive personality traits of the personality inventory for DSM-5. (28th February 2016) - Swami, Viren; Weis, Laura; Lay, Alixe; Barron, David; Furnham, Adrian
Abstract: Conspiracy theories can be treated as both rational narratives of the world as well as outcomes of underlying maladaptive traits. Here, we examined associations between belief in conspiracy theories and individual differences in personality disorders. An Internet-based sample ( N =259) completed measures of belief in conspiracy theories and the 25 facets of the Personality Inventory for DSM-5 (PID-5). Preliminary analyses showed no significant differences in belief in conspiracy theories across participant sex, ethnicity, and education. Regression analyses showed that the PID-5 facets of Unusual Beliefs and Experiences and, to a lesser extent, Suspiciousness, significantly predicted belief in conspiracy theories. These findings highlight a role for maladaptive personality traits in understanding belief in conspiracy theories, but require further investigation. Highlights: Belief in conspiracy theories (BCT) does not vary by basic demographics. BCT is predicted by the PID-5 facet of Unusual Beliefs and Experiences. BCT is predicted by the PID-5 facet of Suspiciousness.